Using Google Jamboard in teacher training and student learning contexts (Journal of Applied Learning and Teaching, 2022)
Keeping social constructivist learning experiences alive in the online classroom is important for our students’ positive learning outcomes. Supporting pedagogies such as collaboration, discovery learning, and the principles of Universal Design for Learning can be facilitated by EdTech tools. One such tool is Google Jamboard, a cloud-based virtual whiteboard. This review of Jamboard focuses on how this simple platform can be used in two contexts: teacher-training sessions within a Scholarship of Teaching & Learning (SoTL) program and by educators in the classroom for student learning activities. The aim of this review is to show illustrative case study examples from around the world of Jamboard in practice, in order to inspire educators to try Jamboard in their own teaching and learning contexts.